The Implications of Marriage on Students' Academic Achievement (A Case Study at STDI Imam Syafi’i Jember): Implikasi Pernikahan terhadap Prestasi Akademik Mahasiswa (Studi Kasus di STDI Imam Syafi’i Jember) - Rafiq Mahir Thalib; Muhammad Rasyid; Harun; Raja Baizar Syah Rafi’u Derajad (Al-Zaujiyyah: Jurnal Hukum Keluarga Islam, 2025)
In human life, marriage is an important event between two people. Academic achievement is a term to indicate the achievement of learning outcomes within a certain period of time through assessments carried out directly by teachers. Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember (STDIIS Jember) is an Indonesian private Islamic university located in Jember Regency. The purpose of this study is to analyze and find the concept of marriage according to ulama' mazhab, the phenomenon of academic achievement of STDI Imam Syafi'i Jember students and the implications of marriage on the academic achievement of STDI Imam Syafi'i Jember students. The approach in this research is to use qualitative methods with the type of research used as a case study. The results of this study show that: The concept of marriage according to ulama' madhab: (1) The law of marriage according to its conditions (B) Harmony and conditions of marriage (1) Husband and wife, (2) Ijab qabul, (3) Guardian, (4) Witness, (5) Ridho. How STDI Imam Syafi'i Jember students can achieve good academic achievements: (1) There is motivation in achieving achievements, (2) Aware of the importance of academic achievement, (3) Understand things that can reduce academic achievement. The implications of marriage on academic achievement are (a) Positive impacts, (b) Negative impacts. Among the positive impacts: (1) More focus, (2) A forum for discussion, (3) Calmer. As for the negative impacts: (1) Time division.